Comparison between fatty acid profiles of old and modern varieties of T. turgidum and T. aestivum: A case study in central Italy. (July 2018) - Tavoletti, Stefano; Foligni, Roberta; Mozzon, Massimo; Pasquini, Marina
Abstract: Old and modern tetraploid ( Triticum turgidum ssp. durum and Triticum turgidum ssp . turanicum ) and hexaploid ( Triticum aestivum ssp . aestivum ) varieties collected in the Marche region (Central Italy) were compared for fatty acid profile of whole grain flour through linear discriminant analysis. Two independent trials were carried out in 2015 and 2016: the first analyzed grain samples collected from organic farmers (old varieties) or wheat storage facilities (modern varieties), the second using grain produced by an experimental field trial, aimed to compare old and modern varieties under identical agronomic and environmental conditions. Multivariate analysis demonstrated that both the most and the least represented fatty acids provided an effective discrimination not only between the main groups ( turgidum vs aestivum ) but also between old and modern varieties within each main group of wheats. Four fatty acids (arachidic, oleic, vaccenic and linolenic) were included in discriminant analysis models of both 2015 and 2016 data sets. Results were consistent between the two years of trial suggesting that the cultivation system (organic or conventional) could influence but did not prevent the discrimination between the old and modern varieties, since the same trend in classification was observed for both tetraploid and hexaploid groups of varieties. Highlights: Fatty acid profile discriminated old from modern wheat varieties. Farming systems did not affect fatty acid profile of whole-wheat flour. Less represented fatty acids improved discrimination of old from modern wheat varieties.